A BIM-based Quantity Calculation Framework for Frame-shear Wall Structure. Issue 2 (3rd April 2019) - Yang, Bin; Zhang, Binghan; Wu, Jie; Liu, Boda; Wang, Zhichen
Abstract: The accuracy of the information on quantities will directly affect the accuracy of the cost. Accurate cost information is the key to avoiding budget overrun, and the use of BIM (Building Information Modelling) in quantity calculations can be more efficient than the traditional method. However, due to the different definitions of the code and the geometry model, BIM-based quantity calculations cannot be directly applied. This paper aims to introduce a framework of a BIM-based quantity calculation method and develop an algorithm that can calculate the quantities of specific structural members based on the Chinese quantity calculation code. This paper discusses the differences between the rules of the Chinese code and those of the geometry model and then translates the rules into an algorithm to make the output of the framework satisfy the requests of the code. A test model is used to assess the accuracy of the results. Finally, this paper summarizes all the work of the development of the quantity calculation framework and offers suggestions for automatic BIM-based quantity calculation.